FPN1–8C>G Polymorphism as a potential genetic modifier of iron overload in transfusion-dependent β-Thalassemia major patients receiving HbF augmentation therapy - Maeesa Wadood; Muhammad Younus Jamal Siddiqui; Iram Nazir; Muhammad Rizwan (Pakistan Journal of Medical Sciences, 2026)
Objectives: To assess the association of the FPN1–8C>G polymorphism with iron overload and iron-regulatory biomarkers in transfusion-dependent β-thalassemia major patients receiving fetal hemoglobin (HbF) augmentation therapy. Methodology: This cross-sectional study was conducted from January 2024 to May 2025 at Fatima Hospital, Baqai Medical University, and Muhammadi Thalassemia Centre, Karachi, Pakistan. A total of 120 transfusion-dependent β-thalassemia major patients receiving hydroxyurea-based HbF augmentation therapy for at least six months were recruited through consecutive sampling. Conventional iron indices and serum hepcidin, erythroferrone (ERFE), growth differentiation factor-15 (GDF-15), and soluble transferrin receptor (sTfR) were measured. PCR-RFLP was performed for FPN1–8C>G genotyping, with Sanger sequencing confirmation. Results: The FPN1–8C>G variant was present in 39 (32.5%) patients. Iron overload was significantly associated with genotype (p=0.012). Variant carriers (CG+GG) had higher odds of iron overload than CC carriers (OR=5.67; 95% CI: 1.60–20.14; p=0.003), and the association remained significant after adjustment for iron-chelation regimen and duration of transfusion exposure (aOR=5.26; 95% CI: 1.43–19.31; p=0.012). Serum iron, ferritin, transferrin saturation, ERFE, and GDF-15 increased across CC, CG, and GG genotypes, whereas TIBC, UIBC, hepcidin, and sTfR decreased (all pG was significantly associated with greater iron burden and altered iron-regulatory biomarkers. It may represent a potential genetic marker of susceptibility to iron overload in transfusion-dependent β-thalassemia major; however, prospective validation is required.